Bivalve shell horizons in seafloor pockmarks of the last glacial‐interglacial transition: a thousand years of methane emissions in the Arctic Ocean. (13th December 2015) - Ambrose, William G.; Panieri, Giuliana; Schneider, Andrea; Plaza‐Faverola, Andreia; Carroll, Michael L.; Åström, Emmelie K. L.; Locke, William L.; Carroll, JoLynn
Abstract: We studied discrete bivalve shell horizons in two gravity cores from seafloor pockmarks on the Vestnesa Ridge (∼1200 m water depth) and western Svalbard (79°00′ N, 06°55′ W) to provide insight into the temporal and spatial dynamics of seabed methane seeps. The shell beds, dominated by two genera of the family Vesicomyidae: Phreagena s.l. and Isorropodon sp., were 20–30 cm thick and centered at 250–400 cm deep in the cores. The carbon isotope composition of inorganic (δ 13 C from −13.02‰ to +2.36‰) and organic (δ 13 C from −29.28‰ to −21.33‰) shell material and a two‐end member mixing model indicate that these taxa derived between 8% and 43% of their nutrition from chemosynthetic bacteria. In addition, negative δ 13 C values for planktonic foraminifera (−6.7‰ to −3.1‰), concretions identified as methane‐derived authigenic carbonates, and pyrite‐encrusted fossil worm tubes at the shell horizons indicate a sustained paleo‐methane seep environment. Combining sedimentation rates with 14 C ages for bivalve material from the shell horizons, we estimate the horizons persisted for about 1000 years between approximately 17, 707 and 16, 680 years B.P. (corrected). The seepage event over a 1000 year time interval was most likely associated with regional stress‐related faulting and the subsequent release of overpressurized fluids. Key Points: Bivalve shell horizons in deep‐sea pockmarks are linked to past methane seepage A major seepage event persisted for ∼1000 years between 17, 707 and 16, 689 years B.P. Shell bed formation is linked to structurally controlled seepage